A rare cause of pulmonary hypertension: bilateral pulmonary artery involvement and stent restenosis due to Takayasu arteritis - Gülten Taçoy; Adnan Abacı; Baran Önal; Şeminur Haznedaroğlu; Ramazan Akdemir (KARE Publishing, 2014)
A 53-year-old female patient was admitted with dyspnea and fatigue. On transthoracic echocardiography, systolic pulmonary artery pressure (PAP) was measured as 90 mmHg, and right heart catheterization revealed pulmonary arterial hypertension. Pulmonary angiography demonstrated bilateral pulmonary artery stenosis, and the diagnosis was determined as Takayasu arteritis. Balloon angioplasty was performed under corticosteroid and immunosuppressive treatment. In this case report, we describe a patient in whom bilateral pulmonary artery stenosis developed due to Takayasu arteritis, and we discuss the patient in light of the current literature.